Fluidity of movement and pedestrian inconvenience in the shopping streets of Brussels - Alexis Creten; Aniss M. Mezoued; Quentin Letesson (Brussels Studies)
Travel on foot has been gaining ground in recent years in debates and in people's thinking due to growing congestion and the negative impacts of the “cars come first” approach on health, the environment and public spaces. In order to promote this form of travel in Brussels, Bruxelles Mobilité carried out a diagnosis of public spaces, through the plans for the accessibility of roads and public spaces [Plans d’accessibilité de la voirie et de l’espace public, PAVE]. The research which this article is drawn from adds to this diagnosis by identifying the broad spectrum of pedestrian inconveniences and variations in how they are perceived. To do this, several distinct methodologies were combined (spatial and morphological analysis, analysis of pedestrian flows and behaviours, itineraries with commentary with people with reduced mobility), thus making it possible to develop a dynamic vision of pedestrian movement and the inconveniences which can affect it. On this basis, several possible solutions are proposed in order to achieve a balance between the need for fluidity of movement, the slowing down of pedestrian flows and the experience of walking.